Responsabilidad social y reputación corporativa en el rendimiento de la Empresa Vickey, año 2023 - Melo Reyes, Omaidy Marianela (2024)
This project on corporate social responsibility (CSR) of the Topsy Ice Cream distribution company, “VICKEY S.A.”, aims to evaluate the incidence of these practices and their effect on the reputation and profitability of the organization. CSR means that companies assume responsibility for their impact on society and the environment, which is why they must act ethically and transparently, taking into account not only their financial objectives, but also the social and environmental consequences of their actions. The methodology used was of a mixed qualitative-quantitative nature, where an instrument was developed that allowed extracting the perceptions of the operational and administrative staff of the organization, through techniques and tools according to the proposed objectives. The development of the project also included the application of interviews, financial analysis and SWOT analysis, which introduced the investigation to an important result for future internal decisions. The results show that more than 50% of the collaborators are unaware of these practices and the terminology of the stakeholders or interest group, which are clients, employees and suppliers in that order, despite the little knowledge of the terminology, they carry it out Empirically, by reusing packaging, it avoids excessive use of paper, through technological equipment and modernizes its means of transportation, in order to strengthen the corporate image and reputation and therefore strengthen financial health and positively affect its profitability.